Implementation of Project-Based Learning in Madrasas: Impact on Student Creativity and Achievement - Labisal Fitri Al - Qolbi (Sekolah Tinggi Agama Islam Kuningan (STAIKuningan), 2025)
The implementation of Project-Based Learning (PjBL) in madrasas offers an innovative approach to increase student creativity and achievement. In the digital era, the need for learning methods that can develop critical thinking, problem-solving, and collaborative skills is increasingly urgent. Madrasas, as a faith-based educational institution, require learning strategies that not only encourage academic understanding but also support character development. This study aims to analyze the impact of the application of PjBL on student creativity and achievement in madrasas. Using a quantitative approach with a pseudo-experimental design, data were collected through creativity tests and achievement tests in the group of students who were given the PjBL intervention and the control group that used traditional learning methods. The results of the study show that PjBL has a significant impact on increasing students' creativity and academic achievement. The PjBL group experienced an increase in creativity by 20% and an increase in academic achievement by 15% compared to the control group. In addition, students in the PjBL group showed higher engagement and strong motivation in completing the project, which favored the creation of more meaningful learning experiences. This research makes a practical contribution to madrasas in adopting PjBL as an effective and relevant learning method to modern educational needs.